The typical Cochrane review. How many trials? How many participants? - Mallett, S; Clarke, M (2002)
OBJECTIVES: To describe the number of trials and participants in a typical systematic review from The Cochrane Database of Systematic Reviews. METHODS: The number of trials in 1,000 Cochrane systematic reviews in issue 1, 2001 of The Cochrane Database of Systematic Reviews was counted for three categories of trial: included trials, ongoing trials, and trials awaiting assessment for inclusion. (The term trial is used in this paper, although a small number of Cochrane reviews include studies that are not trials.) The total number of participants in included trials was extracted from a sample of reviews. RESULTS: A total of 9,778 trials were included in the Cochrane reviews. There were a further 356 ongoing trials and 1,138 trials awaiting assessment for inclusion. A typical review contained six included trials. Forty percent of the reviews listed ongoing trials and/or trials awaiting assessment for inclusion. Based on a sample of 258 reviews, the median number of participants per review was 945 (interquartile range, 313 to 2,511) per review and 118 (interquartile range, 60 to 241) per trial. CONCLUSION: This report is a descriptive study of the number of trials and participants in a typical Cochrane review from The Cochrane Library, issue 1, 2001.